Supply Chain 4.0 Adaptability and Lean Supply Chain Management: Connections and Impact on the Firm’s Operational Performance - Huda, Miftakul; Rahayu, Agus; Furqon, Chairul; Adib Sultan, Mokh; Ahmad, Abdul Aziz (Jurnal Internasional Penelitian Bisnis Terapan, 2025)
The reason of this paper is twofold:to begin with, to supply a estimation device for supply chain adaptability 4.0 by utilizing the hypothetical point of view of ambidexterity to drive Industry 4.0; moment, to observationally analyze how supply chain ambidexterity 4.0 and incline supply chain administration offer assistance move forward firms' operational execution. Observational comes about are gotten through the investigation of study information from a test of 197 outomotif firms that are at the mid-level within the supply chain. Auxiliary condition modeling was conducted to test the three proposed theories. Based on the asset coordination hypothesis and the social resource-based see, this ponder observationally illustrates the fully mediating part of incline supply chain administration within the relationship between supply chain adaptability 4.0 and firm operational performance.